2016
DOI: 10.1115/1.4033923
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Design Parameters on Thermomechanical Stress in Silicon of Through-Silicon Via

Abstract: We examined the effect of the design parameters of a through-silicon via (TSV) on the thermomechanical stress distribution at the bottom of the TSV using finite element analysis. Static analyses were carried out at 350 °C to simulate the maximum thermomechanical stress during postplating annealing. The thermomechanical stress is concentrated in the lower region of a TSV, and the maximum stress in silicon occurs at the bottom of the TSV. The TSV diameter and dielectric liner thickness were two important determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…3 By simulation using ANSYS software, Wang found that the stress at the via bottom is concentrated at the lower region of the TSV, especially at via bottom corner. 15 In the upper region of the TSV, stress is released by the extrusion of copper when annealing. However, at the bottom part, the stress due to the mismatch in TEC between copper and silicon cannot be released.…”
Section: Resultsmentioning
confidence: 99%
“…3 By simulation using ANSYS software, Wang found that the stress at the via bottom is concentrated at the lower region of the TSV, especially at via bottom corner. 15 In the upper region of the TSV, stress is released by the extrusion of copper when annealing. However, at the bottom part, the stress due to the mismatch in TEC between copper and silicon cannot be released.…”
Section: Resultsmentioning
confidence: 99%